Tempo e follia nell’Enrico IV di Marco Bellocchio - Bonanni, Luisa (B@belonline, 2021)
In the movie based on Pirandello’s Henry IV, Marco Bellocchio shows how the central point of this play is not so much madness, but rather time, that time which madness itself allows to go through and relive without constraints. The Madman who pretends to be Henry IV, in fact, apparently tries to give the right sequence to his imaginary life, but he consciously continues to go back and forth in his own events, taking advantage of the fact that in invention – unlike in reality – time is reversible. The speculative component present in Henry IV is thus made explicit by Bellocchio with the strength of the expressive medium he uses, a medium whose potentialities Pirandello was able to evaluate only in a limited way.